Impact of differential detection of TM6SF2 rs58542926 mutation in circulating tumor DNA versus peripheral blood cells on hepatocellular carcinoma patients - Samar Samir Youssef; Eman Abd El Razek Abbas; Mohamed Hassany; Aya Shaaban Ragheb Shaaban; Eman Elsayed Abass Mohammed; Tamer Elbaz (Discover Oncology)
Abstract This study aimed to investigate the differential distribution of the genotypes of the TM6SF2 rs58542926 polymorphism in circulating tumor DNA (ctDNA) versus peripheral blood cells (PBMC) and its association with the development of hepatocellular carcinoma (HCC) in patients infected with the hepatitis C virus (HCV) in Egypt. A total of 147 HCC patients were enrolled in the study, and their genomic and ctDNA were analyzed for the TM6SF2 rs58542926 genotype. The CC genotype was identified as the most common among patients with HCC in Egypt, while the CT genotype was associated with higher serum direct bilirubin, total leucocyte count, and hemoglobin levels than those with the CC genotype. Circulating samples from patients with the CT genotype had significantly higher serum direct bilirubin, ALT, and prothrombin time than those with the CC genotype, as well as a significantly higher percentage of smokers, alcohol intake, and HCV PCR-positive patients. Our findings suggest that lifestyle factors such as smoking and alcohol intake may contribute to the development of HCC in patients with the CT genotype. Both genomic and ctDNA for the TM6SF2 rs58542926 genotype complemented and correlated with parameters of chronic liver disease and underlying risk factors for HCC. Circulating DNA for gene polymorphism provided additional real-time information and more value in correlation with the worsening of liver condition and the presence of HCC risk factors.